Catalytic process development for renewable materials - Imhof, Pieter; Waal, Jan Cornelis van der, 1968- (Weinheim : Wiley-VCH, 2013)
This handbook and ready reference is the first to combine the fields of high throughput experimentation and catalytic process development for biobased materials in industry. It describes the entire workflow from idea, approach, research, and process development, right up to commercialization by application of advanced methodologies and technologies. A large part of the book is devoted to the use of such advanced technologies as high throughput experimentation and equipment, as well as to reactor and process design models, with a wide selection of real life examples included at each stage.
Front Matter -- The Industrial Playing Field for the Conversion of Biomass to Renewable Fuels and Chemicals / Leo E Manzer, Jan Cornelis van der Waal, Pieter Imhof -- Selecting Targets / Gene Petersen, Joseph Bozell, James White -- The Development of Catalytic Processes from Terpenes to Chemicals / Derek McPhee -- Furan-Based Building Blocks from Carbohydrates / Robert-Jan van Putten, Ana Sousa Dias, Ed de Jong -- A Workflow for Process Design : Using Parallel Reactor Equipment Beyond Screening / Erik-Jan Ras -- Braskem's Ethanol to Polyethylene Process Development / Paulo Luiz de Andrade Coutinho, Augusto Teruo Morita, Luis F Cassinelli, Antonio Morschbacker, Roberto Werneck Do Carmo -- Fats and Oils as Raw Material for the Chemical Industry / Aalbert (bart) Zwijnenburg -- Production of Aromatic Chemicals from Biobased Feedstock / David Dodds, Bob Humphreys -- Organosolv Biorefining: Creating Higher Value from Biomass / E Kendall Pye, Michael Rushton -- Biomass-to-Liquids by the Fischer-Tropsch Process / Erling Rytter, Esther Ochoa-Fernández, Adil Fahmi -- Catalytic Transformation of Extractives / Päivi Mäki-Arvela, Irina L Simakova, Tapio Salmi, Dmitry Yu Murzin -- Environmental Assessment of Novel Catalytic Processes Based on Renewable Raw Materials : Case Study for Furanics / Martin K Patel, Aloysius JJE Eerhart, Deger Saygin -- Carbon Dioxide: A Valuable Source of Carbon for Chemicals, Fuels and Materials / Michele Aresta, Angela Dibenedetto -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Catalysis; Chemical engineering; Catàlisi; Energies renovables; SCIENCE -- Chemistry -- Industrial & Technical; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Catalysis; Chemical engineering; Llibres electrònics; Electronic books; Electronic books